Intermediate Korean a grammar and workbook - Byon, Andrew Sangpil (Abingdon, Oxon, [England] Routledge, an imprint of Taylor & Francis, 2021)
"This revised second edition of Intermediate Korean: A Grammar and Workbook is an accessible reference grammar and related exercises in a single volume. The text can be used in conjunction with any primary textbook, both as a reference guide to the intermediate Korean grammar and a practice book to reinforce learning. This book presents twenty-four individual grammar points, covering the core material which students would expect to encounter in their second year of learning Korean. Grammar points are followed by examples and exercises which allow students to reinforce and consolidate their learning. Key features include: clear, accessible format many useful language examples all Korean entries presented in Hangul with English translations abundant exercises with full answer key subject index. Clearly presented and user-friendly, Intermediate Korean provides readers with the essential tools to express themselves in a wide variety of situations, making it an ideal grammar reference and practice resource for students with some knowledge of the language. Intermediate Korean is suitable for both class use as well as independent study."--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Korean language -- Grammar -- Problems, exercises, etc; Korean language -- Textbooks for foreign speakers -- English